Isotope exchange between mercuric [Hg(II)] chloride and Hg(II) bound to minerals and thiolate ligands: Implications for enriched isotope tracer studies. (1st January 2021) - Zhang, Lijie; Liang, Xujun; Wang, Quanying; Zhang, Yaoling; Yin, Xiangping; Lu, Xia; Pierce, Eric M.; Gu, Baohua
Highlights: Rapid Hg isotope exchange is observed in various environmental matrices. Exchange reactions alter distributions and bioavailability of Hg isotopes. Predictions of Hg biogeochemical transformations could be biased if isotope exchange is not considered. Abstract: Enriched mercury (Hg) stable isotopes have been widely used as tracers in field and laboratory investigations of Hg(II) biogeochemical transformations such as methylation and demethylation. Few studies, however, have considered concurrent isotope exchange reactions between newly spiked and pre-existing Hg(II) in environmental matrices, which may alter redistribution and thus transformation of the spiked and pre-existing Hg(II). Using enriched 198 Hg [as mercuric Hg(II) or HgCln species], this study investigated isotope exchange between 198 Hg and pre-existing Hg(II) bound to metacinnabar (β-HgS), sediments, low-molecular-weight (LMW) thiols, and dissolved organic matter (DOM). The impact of isotope exchange on methylmercury production in the presence of organic ligands was also evaluated with an iron-reducing bacterium Geobacter sulfurreducens PCA in a phosphate buffered solution (pH 7.4). We found that spiked 198 Hg readily exchanged with mineral-bound ambient Hg(II) despite concurrent Hg(II) adsorption and immobilization on the solids. Rapid exchange (<3 min) was also observed between spiked 198 Hg and 200 Hg pre-equilibrated with LMW thiols and DOM in solution. While the exchange did not cause net changes in Hg(II) chemical speciation, it resulted in redistribution of Hg(II) isotopes bound to the ligands and thus an apparently similar methylation rate and magnitude of the spiked 198 Hg and pre-existing 200 Hg by PCA cells when 198 Hg and 200 Hg were added at 1:1 ratio. These observations underscore the importance of isotope exchange when an enriched Hg isotope is applied in environmental matrices, as the exchange could potentially lead to biased rate calculations of Hg(II) transformation and bioaccumulation and thus risk assessments of new Hg(II) input to the natural ecosystems.